2018
DOI: 10.1177/0957650918778661
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of leading edge flow characteristics in a mixed flow turbine under pulsating flows

Abstract: Current trends in the automotive industry towards engine downsizing means turbocharging now plays a vital role in engine performance. A turbocharger increases charge air density using a turbine to extract waste energy from the exhaust gas to drive a compressor. Most turbocharger applications employ a radial inflow turbine. However, to ensure radial stacking of the blade fibers and avoid excessive blade stresses, the inlet blade angle must remain at zero degrees, creating large incidence angles. Alternately, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The impact of rotor inlet flow condition were studied by Lee et al 8 over a wide range of pulsating flow conditions. The authors showed that the LE span-wise flow distribution varied over the pulse period and was dependent on the pulse characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of rotor inlet flow condition were studied by Lee et al 8 over a wide range of pulsating flow conditions. The authors showed that the LE span-wise flow distribution varied over the pulse period and was dependent on the pulse characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Abidat et al [13] studied the clearance effect between the rotor blades and the casing on the mixed turbine performance. In two cases, papers [14,15] studied the effects of the cone and the inlet blade angles on mixed inflow turbine performance. The first is for a fixed outlet volute section and the second for a variable outlet volute section.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee et al, [15] stated the presence of axial flow element at the inlet rotor was discovered to obtain swallowing capacity than the radial flow element as it is mainly due to the variation of distribution of an incidence at the respective location. Lee et al, [16] further stated that the efficiency at low velocity ratio and loss correlated to the flow angle could be improve with the use of a mixed flow turbine. Leonard et al, [17] found a significant presence of secondary flow and loss at highly incidence angle as the flow enter the rotor.…”
Section: Introductionmentioning
confidence: 99%